PANDANGAN PADA REALITAS 4 DAERAH : ANALISIS NILAI-NILAI PENDIDIKAN DENGAN TINJAUAN ANTROPOLOGIS - Dynar Puspa Wulandari; Najwa Putri Aulia; Efendi Santoso; Adhelia Puspita Sari; Kartika Salma, Sinta (CV. Supernova Office Stationary and Printing, 2024)
The basic concept of anthropology can also involve several aspects such as recognizing cultural diversity. It should be reminded that in Indonesia itself there are 38 provinces so they consist of various ethnic groups, languages and religions, each of which has its own culture. There is a lot of diversity in Indonesia, Indonesia itself has a motto, namely